2021
DOI: 10.1016/j.ymgmr.2021.100782
|View full text |Cite
|
Sign up to set email alerts
|

Case report: ‘AARS2 leukodystrophy’

Abstract: Background Mitochondrial alanyl-tRNA synthetase 2 gene ( AARS2 ) related disease is a rare genetic disorder affecting mitochondrial metabolism, leading to severe cardiac disease in infants or progressive leukodystrophy in young adults. The disease is considered ultra-rare with only 39 cases of AARS2-leukodystrophy previously reported. Case presentation We present the case of a young man of consanguineous heritage suffering from cognitive decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The 63 cases reported to date involved a constellation of symptoms including tremor, personality change, dementia, reduced mobility, and leukodystrophy, with progressive symptomatic worsening and reduced functional capacity. 9 The typical phenotype described is consistent with the case reported here and includes a mean age at presentation of 29 years, initial psychiatric symptoms coupled with cognitive decline, parkinsonism, ataxia, tremor, pyramidal signs, and seizures, followed by severe and rapid motor decline. Nystagmus has been reported in other forms of leukodystrophy, diagnosed in both childhood 10 and adult life 11 ; however, unlike the case reported here, leukodystrophy-associated childhood-onset nystagmus is typically observed in the context of a wider clinical phenotype including global developmental delay and central hypotonia.…”
Section: Discussionsupporting
confidence: 86%
“…The 63 cases reported to date involved a constellation of symptoms including tremor, personality change, dementia, reduced mobility, and leukodystrophy, with progressive symptomatic worsening and reduced functional capacity. 9 The typical phenotype described is consistent with the case reported here and includes a mean age at presentation of 29 years, initial psychiatric symptoms coupled with cognitive decline, parkinsonism, ataxia, tremor, pyramidal signs, and seizures, followed by severe and rapid motor decline. Nystagmus has been reported in other forms of leukodystrophy, diagnosed in both childhood 10 and adult life 11 ; however, unlike the case reported here, leukodystrophy-associated childhood-onset nystagmus is typically observed in the context of a wider clinical phenotype including global developmental delay and central hypotonia.…”
Section: Discussionsupporting
confidence: 86%
“…AARS2 -related leukoencephalopathy is reportedly less common than CSF1R -related leukoencephalopathy. With approximately 40 cases caused by AARS2 gene mutations have been reported in the literature [ 20 ], we have just begun to recognize the wide genetic and phenotypic spectrum related to AARS2 gene mutations. The whole-exome sequencing has emerged as a powerful approach in the diagnosis of adult-onset leukoencephalopathies, and more collaborative efforts are needed in order to improve better therapeutic management.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have also identified recessive mutations in alanyl-transfer (t)RNA synthetase 2 (AARS2) gene, which encodes a tRNA synthetase responsible for correctly loading alanine onto tRNA-ala for the translation of mitochondrial proteins. AARS2 mutation carriers developed ALSP with an average age of onset around 29 years of age (range 15-44 years) (Lynch et al, 2016(Lynch et al, , 2017(Lynch et al, , 2019Taglia et al, 2018;Wang et al, 2018;Axelsen et al, 2021). It is intriguing why these two seemingly unrelated genes, CSF1R and AARS2, give rise to the same leukodystrophy.…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%